Unemployment among Graduates - Is there a Mismatch? - Kadir, Juliana Mohd Abdul; Naghavi, Navaz; Subramaniam, Geetha (International Journal of Asian Social Science, 2020)
Malaysian graduates have been challenged with issues of unemployment with an increasing trend in unemployment rates in the last few years. The increasing unemployment rate is a grave concern since this issue may decrease the image of the educational system in Malaysia and hence might lead to some companies losing their confidence in our local graduates. Hence, the root cause of this issue needs immediate attention. This paper examines the link between graduate attributes, employability skills, English proficiency, unrealistic salary and job mismatch on unemployment among graduates in Malaysia. Using a self-administered questionnaire, data was collected from 159 workers who had graduated from public universities in Shah Alam and experienced unemployment for at least six months from the date they completed their studies. Partial least squares method has been adopted using SmartPLS 3.0 software for analyzing the data. The findings revealed that employability skills, job mismatch and unrealistic salary were the main factors causing unemployment among graduates. To mitigate this issue, policy measures have to look at both micro level in terms of attitude of graduates as well as macro level at institutional factors such as courses provided by the universities.